The evolutionary history of Eugenia sect. Phyllocalyx (Myrtaceae) corroborates historically stable areas in the southern Atlantic forests - de Oliveira Bünger, Mariana; Mazine, Fiorella Fernanda; Forest, Félix; Bueno, Marcelo Leandro; Stehmann, João Renato; Lucas, Eve J. (Annals of botany, 2016)
Eugenia sect. Phyllocalyx Nied. includes 14 species endemic to the Neotropics, mostly distributed in the Atlantic coastal forests of Brazil. Here the first comprehensive phylogenetic study of this group is presented, and this phylogeny is used as the basis to evaluate the recent infrageneric classification in Eugenia sensu lato (s.l.) to test the history of the evolution of traits in the group and test hypotheses associated with the history of this clade. A total of 42 taxa were sampled, of which 14 were Eugenia sect. Phyllocalyx for one nuclear (ribosomal internal transcribed spacer) and four plastid markers (psbA-trnH, rpl16, trnL-rpl32 and trnQ-rps16). The relationships were reconstructed based on Bayesian analysis and maximum likelihood. Additionally, ancestral area analysis and modelling methods were used to estimate species dispersal, comparing historically climatic stable (refuges) and unstable areas. Maximum likelihood and Bayesian inferences indicate that Eugenia sect. Phyllocalyx is paraphyletic and the two clades recovered are characterized by combinations of morphological characters. Phylogenetic relationships support a link between Cerrado and south-eastern species and a difference in the composition of species from north-eastern and south-eastern Atlantic forest. Refugia and stable areas identified within unstable areas suggest that these areas were important to maintain diversity in the Atlantic forest biodiversity hotspot. This study provides a robust phylogenetic framework to address important historical questions for Eugenia s.l. within an evolutionary context, supporting the need for better taxonomic study of one of the largest genera in the Neotropics. Furthermore, valuable insight is offered into diversification and biome shifts of plant species in the highly environmentally impacted Atlantic forest of South America. Evidence is presented that climate stability in the south-eastern Atlantic forest during the Quaternary contributed to the highest levels of plant diversity in this region that acted as a refugium.